Within the Realms of Uncertainties: Phenomenologizing the Lived Experiences of Covid-19 Survivors - Zera Nacod-am; Anthoinette Bubod; Sarah Lunag; Jessa Muriel Calatan; Donato O. Abaya (Journal of Arts, Humanities and Social Science)
The COVID-19 pandemic has undoubtedly been triggering mental health issues. One of the worst scenarios is to become severely ill due to the COVID-19 virus, which may put someone in a life-threatening situation that may be traumatic and could affect one’s psychological well-being. This study explored the lived experiences of COVID-19 survivors before, during, and after they were infected with the COVID-19 virus using a qualitative approach, particularly transcendental phenomenology. Data was collected among 10 COVID-19 survivors through face-to-face interviews and was analyzed using Moustakas' transcendental phenomenology and analysis procedures. In the exploration of the lived experiences of the COVID-19 survivors, four themes have emerged: 1) surfacing psychological distress, 2) extreme psychological distress, 3) realizing the value of life, and 4) facing the challenges of discrimination. Two overarching themes have emerged: 1) embracing optimism and 2) boosting faith and spirituality. The remarkable outcome of this study was the development of an onion model of the lived experiences of COVID-19 survivors, which presents the connection of their experiences before, during, and after they were infected with the COVID-19 virus. It describes that the COVID-19 survivors, although they experienced life-threatening situations, remain hopeful with their outlook in life, believing that the Divine will not forsake them. It is recommended that COVID-19 survivors may undergo appropriate psychological intervention that could help them get away from the possibility of having future mental health issues.